THE CORRELATION BETWEEN KNOWLEDGE WITH ATTITUDES OF ADOLESCENTS IN CONSUMING IRON TABLETS AT SMP NEGERI 2 KABANJAHE, KABANJAHE DISTRICT, KARO REGENCY IN 2023 - Srilina Br Pinem; Ninsah Mandala Putri Sembiring; Marlina Simbolon; Ernamari Ernamari; Srievadiana Br. Sembiring; Pita Nova Br. Ginting (International Journal of Midwifery Research, 2023)
Lack of iron in adolescents without balanced adequate iron intake will continue during pregnancy when pregnancy will cause fetal growth is not optimal, low birth weight, the risk of bleeding during labor and increase the risk of maternal and infant death. Therefore most Obstetrics and Nutrition experts recommend iron supplements from preconception (adolescence). This was an analytical research with a Cross Sectional design, where researchers take samples from a population using a questionnaire as a data collection tool to determine the relationship between knowledge and attitudes of adolescents in consuming iron tablets at SMP Negeri 2 Kabanjahe, Karo Regency, North Sumatra Province in 2023. Results of a study conducted by the author entitled "The Relationship of Knowledge and Attitudes of Adolescents in Consuming Iron Tablets at SMP Negeri 2 Kabanjahe, Karo Regency, North Sumatra Province in 2023". By measuring the knowledge and attitudes of adolescents in consuming Iron Tablets. This research by looking at secondary data, data obtained from SMP Assisi is like looking at the number of adolescent girls. The conclusion of the statistical test results is obtained p value = 0.000 (p <0.05). This means that there is a significant relationship between knowledge and attitudes of adolescents in taking iron tablets.